Pengelolaan Kurikulum Sekolah Alam di SD Alam Al-Izzah Krian Sidoarjo - Lutfiyah, Uhwatul; Yuliana, Ivo; Bahrozi, Imam (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
Natural school is an alternative to nature-based education by utilizing natural resources around the environment, especially school’s environment. This study aims to observe and describe the management of the natural school curriculum implemented at SD Alam Al-Izzah, which is located in Krian District, Sidoarjo Regency, East Java. Management of the implemented curriculum includes planning, implementation, and evaluation. This study uses a descriptive qualitative approach. Data collection techniques used include interviewa, observation, and documentation. With data analysis in the form of triangulation. The research result include; 1) the planning stage, the curriculum used is a combination og=f the national curriculum and the natural school curriculum based on four pillars namely morals, logic, leadership, and business, 2) the implementation stage of the curriculum focuses on learning prpgrams in character education, moral, and tahfidz, 3) evaluation stage the curriculum is held every weekend and at the end of the semester. The results of this study are expected to be used as a reference in implementing and managing curriculum in nature-based schools in a better direction.